Regulation of SUMOylation by reversible oxidation of SUMO conjugating enzymes - Bossis, Guillaume; Melchior, Frauke (Molecular cell, 2006)
Posttranslational modification with small ubiquitin-related modifier (SUMO) has emerged as a central regulatory mechanism of protein function. However, little is known about the regulation of sumoylation itself. It has been reported that it is increased after exposure to various stresses including strong oxidative stress. Conversely, we report that ROS (reactive oxygen species), at low concentrations, result in the rapid disappearance of most SUMO conjugates, including those of key transcription factors. This is due to direct and reversible inhibition of SUMO conjugating enzymes through the formation of (a) disulfide bond(s) involving the catalytic cysteines of the SUMO E1 subunit Uba2 and the E2-conjugating enzyme Ubc9. The same phenomenon is also observed in a physiological scenario of endogenous ROS production, the respiratory burst in macrophages. Thus, our findings add SUMO conjugating enzymes to the small list of specific direct effectors of H2O2 and implicate ROS as key regulators of the sumoylation-desumoylation equilibrium.